ISLAMIC JOURNALISTIC ETHICS IN REPORTING STUDENT SUICIDES ON DETIK.COM: A SOCIAL RESPONSIBILITY PERSPECTIVE - Labiba, Fikriya; Salama, Nadiatus (al-Balagh : Jurnal Dakwah dan Komunikasi, 2025)
The reporting of suicide cases poses the risk of triggering copycat behavior, known as the Werther Effect. While many studies have examined media compliance with reporting guidelines and the impact on audiences, few have explored how Islamic journalistic values can offer ethical alternatives. This study introduces a new perspective by integrating Islamic journalistic ethics with social responsibility theory to evaluate the quality of suicide case reporting in online media. Using a qualitative, descriptive approach within a constructivist paradigm, data were collected through interviews with journalists and editors from Detik.com’s Central and East Java offices, alongside an analysis of student suicide news published between August and October 2024. Findings show that Detik.com emphasizes accuracy, neutrality, and verification through credible sources. Articles include warnings to reduce the risk of imitation and protect victims’ privacy, while also providing space for family clarification. These practices align with Islamic values such as ṣidq (truthfulness), tabayyun (verification), ‘adl (justice), amar ma’rūf nahī munkar, and amanah (trustworthiness). The study recommends journalist training on mental health issues and developing a comparative analysis across online media platforms to gain a more comprehensive overview.